ФІЛОСОФСЬКИЙ АНАЛІЗ ПОСТСТРУКТУРАЛІСТСЬКИХ ІНТЕРПРЕТАЦІЙ БІБЛІЇ - Повторева, С. М. (The Journal of V. N. Karazin Kharkiv National University. Series "Theory of Culture and Philosophy of Science", 2015)
У статті розглядаються особливості деконструкції біблейських текстів в дискурсивнихпрактиках постструктуралізму. Показано, як постструктуралістський методологічний принципвідмінності змінює традиційні уявлення про Біблію і сприяє оновленню інтересу наших сучасниківдо істин Священного Писання.Повторева С.М. Философский аналіз постструктуралистских интерпретаций Библии. Встатье рассматриваются особенности деконструкции библейских текстов в дискурсивныхпрактиках постструктурализма. Показано, как постструктуралистский методологическийпринцип отличия изменяет традиционные представления о Библии и способствует обновлениюинтереса наших современников к истинам Священного Писания.Ключевые слова: деконструкция, нарратив, отличие, постструктурализм, чужак.Povtoreva S.M. Tне Philosophical Analysys of the Poststructuralist Interpretation of Bible. Inthe article devoted the character of deconstruction of Bible texts in the poststructuralist discoursepractice. The author demonstrated as the methodological principle of difference changes the traditionalunderstandings of Bible and helps to renovate the interest of modern people to the truth of HolyScripture.Key words: deconstruction, difference, narrative, poststructuralism, journeying strange.